The Effect of the Gradual Activities Strategy on the Performance of Some Complex Offensive Skills of Handball for Students - Kadhem, Abbas Abdulhamza; Mahdi, Jaafar Ahmed; Abbood, Adnan Mohsin (Journal of Social Work and Science Education, 2025)
The purpose of the study is to determine the impact of the gradual activities’ strategy on students’ performance of certain offensive handball skills as well as whether the experimental and control groups’ effects on students’ performance of these skills are superior in the post-test. By creating two identical groups (experimental and control) with pre- and post-tests, the researcher employed the experimental technique to fit the nature of the research problem. For the 2023–2024 academic year, 90 second-year students from the University of Karbala’s College of Physical Education and Sports Sciences were part of the research community. A total of 40 students were chosen for the study and split into two groups: an experimental group and a control group, each with 20 students. The statistical package (SPSS) was used to statistically process the data for the variables being studied. Using educational units based on the gradual activities’ strategy has a significant impact on students’ development of the complex offensive skills under study and their motivation to perform some of the more difficult offensive skills in handball, according to one of the researcher’s most significant findings. Using educational units in accordance with the gradual activities’ strategy, which greatly aided students in developing the complex offensive skills under study, and the necessity of implementing contemporary study techniques because they improve learning levels were the researcher’s two most important recommendations.